The structure of rare earth thin films: holmium and gadolinium on yttrium - Bentall, M; Cowley, R; Ward, R; Wells, MR; Stunault, A (2003)
Single-crystal holmium and gadolinium layers have been grown on yttrium substrates using the molecular beam epitaxy technique and their structures investigated using high resolution x-ray scattering. The experiments were performed using a Philips MRD diffractometer in Oxford, and with the XMaS facility at the ESRF. Holmium layers with a thickness below Tc′ = 115 Å give scattering that is characteristic of a pseudomorphic film structure with the same in-plane lattice parameter as the yttrium substrate to within 0.05%. For layers thicker than Tc′, there is a sharp reduction in misfit strain due to the creation of edge dislocations. The transverse lineshape of the holmium peaks exhibits a two-component lineshape for thicknesses above Tc′, but below about 500 Å. Above 500 Å the lineshape of the transverse scans becomes Gaussian and is characteristic of a mosaic crystal. The gadolinium layers show no sharp change of strain for layers as thick as 2920 Å and the transverse peak shape remained similar for all films. This is characteristic of pseudomorphic film growth and a failure to nucleate dislocations.